Cultural Dynamics of Islamic Banking in Libya: Overcoming Regulatory Fragmentation and Enhancing Financial Literacy - Aljadi, Soliman; Mayhub, Abdul Razak; Ahmoudah, Ali (Institut Agama Islam Negeri Parepare, 2025)
Purpose – This study aims to examine the integration of Islamic banking in Libya, focusing on cultural relevance, regulatory challenges, and economic impact Method – Using a qualitative approach, data was collected through stakeholder interviews, case studies from Malaysia and the UAE, and policy analysis to assess the factors influencing Islamic financial adoption in Libya. Findings – The findings indicate that Islamic banking aligns with Libya’s socio-cultural values, yet regulatory inconsistencies and limited financial literacy hinder widespread adoption. The study confirms that Sharia-compliant microfinance products enhance financial inclusion, particularly for rural and unbanked populations, but digital banking infrastructure remains underdeveloped. Practical implications – Theoretically, the study contributes to Institutional Theory, Maqashid Sharia Framework, and Financial Inclusion Theory, demonstrating the role of regulatory governance and cultural adaptation in financial sustainability. Practically, the findings suggest that Libya should establish a centralized Sharia advisory body, implement targeted financial literacy programs, and invest in Islamic fintech solutions. Originality/value – The originality of this study lies in its comparative analysis of Libya’s Islamic banking sector and its integration of cultural financial practices into modern Islamic finance models